IMPLEMENTATION OF GROUP GUIDANCE IN OVERCOMING STUDENTS DIFFICULTY IN MAN DAIRI - Tuppak Padang, Saiful Akhyar Lubis2, Edi Saputra (Pascasarjana UIN Sumatera Utara, 2019)
Abstract: The purpose of this study was to determine, 1) the implementation of group guidance inovercoming student learning difficulties at MAN Dairi, 2) supporting and inhibiting factors in implementinggroup guidance in overcoming student learning difficulties at MAN Dairi, 3) the effectiveness ofgroup guidance in overcoming student learning difficulties at MAN Dairi. The approach used is descriptivequalitative data collection techniques using observation, interviews, and documentation. The findingsof this study are 1) The implementation of group guidance at MAN Dairi in overcoming students‘learning difficulties is carried out by creating categories for students who have problems and studentswho have achievements. So that in the community or group it will be clearly seen how to approachstudents who do have problems and need solutions, or students who do need more motivation todevelop their potential towards better, 2) As for the supporting factors in the implementation of guidancegroups in overcoming student learning difficulties are: a) sufficient number of BK teacher personnel andclear division of tasks, b) Good coordination between BK teachers, homeroom teachers, MadrasahHead Assistants (PKM/WKM), Madrasah Principals and parents of students, c) Resolving problemsquickly. Meanwhile the inhibiting factors in the implementation of group guidance in overcoming studentlearning difficulties are: a) Internal factors (originating from within the students themselves), b)Student‘s residence is relatively far from school, c) Muslim minority environment, and 3) while theeffectiveness of implementing group guidance in overcoming student learning difficulties has a verysignificant impact especially in terms of reducing or solving their problems. Besides, the group guidanceprogram also functions in developing students’ potential towards becoming even better.Keywords: Implementation, Group guidance, Students dificulty